2009
DOI: 10.1074/jbc.m805805200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the P2X7 Receptor Increases the Ca2+ Content of the Endoplasmic Reticulum, Activates NFATc1, and Protects from Apoptosis

Abstract: The P2X 7 receptor is known for the cytotoxic activity because of its ability to cause opening of non-selective pores in the plasma membrane and activate apoptotic caspases. A key factor of P2X 7 -dependent cytotoxicity is the massive intracellular Ca 2؉ increase triggered by its activation. Here we show that P2X 7 transfection increased the ability of the endoplasmic reticulum to accumulate, store, and release Ca 2؉ . This caused a larger agonist-stimulated increase in cytosol and mitochondrial Ca 2؉ in P2X 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 50 publications
6
109
0
1
Order By: Relevance
“…Considering that the activation of P2X 7 receptor inhibits the PPI-PLC signaling pathway [21] it might look paradoxical that the response coupled to P2Y receptors was larger in cells expressing the P2X 7 receptor. The group of Di Virgilio has very recently reported that transfection of HEK293 cells with P2X 7 receptors increased their capacity to accumulate calcium in the endoplasmic reticulum [22]. As a consequence, the agonists mobilizing this intracellular pool of calcium (carbachol or bradykinin in their hands) provoked a larger increase in the cytosolic concentration of calcium in the cells expressing the P2X 7 receptor than in cells which did not express it.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the activation of P2X 7 receptor inhibits the PPI-PLC signaling pathway [21] it might look paradoxical that the response coupled to P2Y receptors was larger in cells expressing the P2X 7 receptor. The group of Di Virgilio has very recently reported that transfection of HEK293 cells with P2X 7 receptors increased their capacity to accumulate calcium in the endoplasmic reticulum [22]. As a consequence, the agonists mobilizing this intracellular pool of calcium (carbachol or bradykinin in their hands) provoked a larger increase in the cytosolic concentration of calcium in the cells expressing the P2X 7 receptor than in cells which did not express it.…”
Section: Discussionmentioning
confidence: 99%
“…The trophic signaling cascade activated by P2X7 involves subtle changes in intracellular Ca 2þ homeostasis, stimulation of mitochondrial metabolism, activation of NFATc1, and suppression of apoptosis (8,9). NFATc1, a key transcription factor in lymphocyte division and cancer cell growth, exerts a central role in P2X7-mediated proliferation as it is strongly upregulated in HEK293 cells expressing different P2X7 isoforms (9,12), and its blockade by selective inhibitors, such as cyclosporine or VIVIT, obliterates P2X7-dependent cell growth (9).…”
Section: þmentioning
confidence: 99%
“…NFATc1, a key transcription factor in lymphocyte division and cancer cell growth, exerts a central role in P2X7-mediated proliferation as it is strongly upregulated in HEK293 cells expressing different P2X7 isoforms (9,12), and its blockade by selective inhibitors, such as cyclosporine or VIVIT, obliterates P2X7-dependent cell growth (9). P2X7 expression not only stimulates growth but also enhances invasiveness of HEK293 cells, as shown in vitro, in Matrigel infiltration experiments (12), and in vivo, in a zebrafish model of metastasis (30).…”
Section: þmentioning
confidence: 99%
See 2 more Smart Citations